The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1186/1749-8090-7-89
|View full text |Cite
|
Sign up to set email alerts
|

EuroScore 2 for identification of patients for transapical aortic valve replacement - a single center retrospective in 206 patients

Abstract: BackgroundOperative risk scoring algorithms identify patients with severe AS for transcatheter valve implantation in whom the anticipated operative mortality for conventional surgery would be considered prohibitive. We compared the three risk scores EuroScore 1 (LES), society of thoracic surgeons’ (STS) score and ACEF (age-creatinine-ejection fraction score) to the readjusted EuroScore 2 recently presented.MethodsWe reviewed all consecutive patients receiving either isolated conventional aortic valve replaceme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 17 publications
1
9
0
2
Order By: Relevance
“…Indeed, prediction of mortality rates in patients evaluated for TAVI differs considerably among different scoring systems with conflicting results among different studies. In transapically treated patients, the study by Haensig et al [18] showed that the STS-PROM score was a better predictor of 30-day mortality than the new EuroScore II, while another study did not confirm these results [19]. In the two most recent studies including both transapically and transfemorally treated patients, the EuroScore II tended to perform better with regard to discriminatory power compared to the logistic EuroScore and the STS-PROM score, in particular in the transfemorally treated patient cohort [20,21].…”
Section: Introductionmentioning
confidence: 61%
“…Indeed, prediction of mortality rates in patients evaluated for TAVI differs considerably among different scoring systems with conflicting results among different studies. In transapically treated patients, the study by Haensig et al [18] showed that the STS-PROM score was a better predictor of 30-day mortality than the new EuroScore II, while another study did not confirm these results [19]. In the two most recent studies including both transapically and transfemorally treated patients, the EuroScore II tended to perform better with regard to discriminatory power compared to the logistic EuroScore and the STS-PROM score, in particular in the transfemorally treated patient cohort [20,21].…”
Section: Introductionmentioning
confidence: 61%
“…En un estudio publicado en Alemania en el que se especifican las necesidades de transfusión según el tipo de cirugía, los pacientes en los que se realizaba sustitución valvular aórtica necesitaron una media de 3,6 ± 6,9 concentrados de hematíes, y en aquellos en los que se realizó TAVI las necesidades de sangre fueron 1±2,6 concentrados de hematíes 218 . En otro estudio centrado en población de edad avanzada en Australia se observo que el 76% de la población general necesito ser transfundido 256 .…”
Section: Discussionunclassified
“…En el caso de aplicar el modelo americano, se consideran candidatos a TAVI a aquellos pacientes cuyo valor de STS es mayor de 10. Sin embargo se ha visto que no existe concordancia entre los modelos, ya que al aplicarlo sobre una misma población el número de pacientes clasificados "de alto riesgo" por el Euroscore es mucho mayor el obtenido por el STS 218 . El problema de utilizar modelos con problemas de calibración para tomar este tipo de decisiones es que la infraestimación del riesgo deja a muchos pacientes fuera del tratamiento conservador, mientras que la sobreestimación del riesgo producida por el Euroscore Log condena a algunos pacientes a un tratamiento conservador cuando en realidad se podían beneficiar de un tratamiento convencional con AVR 223 .…”
Section: Escalas De Gravedad Utilizadas En Cirugiaunclassified
“…26,[132][133][134][135] In a recent report, Van Mieghem et al 136 proposed a new risk stratification model specially designed for patients undergoing TAVR, the so-called SURTAVI model. The proposed model includes not only common variables found in previous risk models such as age, diabetes mellitus, renal insufficiency, cerebrovascular disease, but also variables that seem to affect outcomes in patients undergoing TAVR such as frailty, the presence of a porcelain aorta, a complex chest deformity, previous extensive mediastinal radiation, and advanced liver failure.…”
Section: Patient Assessment and Risk Stratificationmentioning
confidence: 99%